2015
DOI: 10.1109/tit.2015.2399914
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity-Based Recovery of Finite Alphabet Solutions to Underdetermined Linear Systems

Abstract: We consider the problem of estimating a deterministic finite alphabet vector f from underdetermined measurements y = Af , where A is a given (random) n × N matrix. Two new convex optimization methods are introduced for the recovery of finite alphabet signals via 1-norm minimization. The first method is based on regularization. In the second approach, the problem is formulated as the recovery of sparse signals after a suitable sparse transform. The regularization-based method is less complex than the transform-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…O(L M ). Remark 2: It is worth noting that the equivalence between the ℓ 0 -norm and ℓ 1 -norm in (P 1 ) hold only for the noiseless case as shown in [11], and not in our case. That is why performance loss are obtained as will be shown hereafter.…”
Section: A Relaxed Minimization Problemmentioning
confidence: 68%
See 1 more Smart Citation
“…O(L M ). Remark 2: It is worth noting that the equivalence between the ℓ 0 -norm and ℓ 1 -norm in (P 1 ) hold only for the noiseless case as shown in [11], and not in our case. That is why performance loss are obtained as will be shown hereafter.…”
Section: A Relaxed Minimization Problemmentioning
confidence: 68%
“…This gain becomes more important for 16-QAM constellation, it is about 3dB at BER 10 −2 , and 3.7dB at BER 10 −2 . The reason for the BER gain growth with the constellation size is that, the accuracy of the ℓ 0 -norm relaxation by the ℓ 1 -norm highly depends on the system dimensions and the sparsity threshold of the signal vector [11].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Source separation Since the output of the first decomposition is a sparse vector that contains a majority of zero elements, the detection of the original information can be seen as a sparse source decoding. In this context, the authors in [7] demonstrated that the vector x can be recovered by resolving the following optimization problem:…”
Section: Proposed Half-sparse Decompositionmentioning
confidence: 99%
“…Previous works proved that source separation is possible in the underdetermined case thanks to basis pursuit (BP) technique [6]. Following this approach, a sparse representation was proposed in [7] to define a successful separation method for a conditioned dimension system. Underdetermined noisy MIMO system with finite alphabet was dealt with as an application case of [7] in [1] and [8], where the problem was formulated as a basis pursuit denoising (BPDN) problem with relaxed constraints.…”
Section: Introduction Dmentioning
confidence: 99%
See 1 more Smart Citation